Distribution and chromosomal polymorphism of the malaria vector Anopheles dirus species D. - V. Baimai (2018)
Preliminary results indicate that species D of the Anopheles dirus complex is widespread west of the Thai-Burma border in Burma and Bangladesh. A chromosomal study of An. dirus species D in these areas has revealed that this malaria vector is highly polymorphic for chromosomal rearrangements in salivary gland polytene chromosomes. The data from the limited number of wild-caught samples suggest that different geographically isolated populations may occur with respect to the frequency of inversions 2La, 3Ra and 3La. The distribution of chromosomal polymorphisms may be associated with the geography and epidemiology of human malaria in this region.